Investigation of the trends and variability in rainfall pattern in the Upper Kumaon Himalayan region - Anand, Subhash; Aarti,; Singh, Anju (Frontiers in Climate, 2025)
Variation in rainfall patterns has profound impacts on fragile ecosystems and people’s lives. The Upper Kumaon area is highly sensitive to current climatic variation. This study attempted to identify yearly, seasonal, and monthly rainfall trends in four districts of the Upper Kumaon Region (UKR), i.e., Almora, Bageshwar, Champawat, and Pithoragarh, for a period of 68 years (1950–2018). Long-term gridded daily rainfall data were used for parametric regression analysis and variability analysis to examine historical trends. The analysis showed a continuous decrease in annual precipitation across all districts, with the most significant decrease seen at Bageshwar (−3.88 mm/year). Seasonal trends showed significant decreases in monsoon rainfall, especially in Almora (−3.28 mm/year), whereas spatial variability analysis depicted increasing variability in recent times. Lower-altitude districts (i.e., Champawat) exhibit higher variability compared to high-altitude districts such as Pithoragarh. Therefore, the findings of this study emphasize the need to implement policies to address the increasing variability in rainfall and its effects on agricultural practices, water resource management, and disaster preparedness in this sensitive environment.